Broadway Danny Rose [videorecording (DVD)] - Allen, Woody, 1935-; Allen, Woody, 1935-; Farrow, Mia, 1945-; Forte, Nick Apollo (Woody Allen collection., 2001)
Comedy about an agent Broadway Danny Rose and his attempt to revive the sagging career of the overweight, aging lounge singer, Lou Canova. Danny has finally booked Lou at the Waldorf, but Lou won't go on unless his girlfriend Tina is there on opening night. It's Danny's quest to round up Tina, an attempt that lands him right in the middle of a gangland battle.